#TITLE_ALTERNATIVE# - PRATIWI (NIM: 30715009), RIMADANI
Heavy metals are an element that is widespread distributed in the environment and a few of these metals are essential to life. However, abnormal level of them has been associated with the toxicity for a human being. Lead (Pb), cadmium (Cd), mercury (Hg), tin (Sn), arsenic (As), and copper (Cu) are several heavy metals which can contaminate food and drinking water. As the result, they have a maximum allowable level in food and drinking water. Numerous analytical methods have been developed for their detection with atomic absorption spectroscopy (AAS) and inductively coupled plasma mass spectrometry (ICPMS) being the most common. While AAS and ICPMS are sensitive and selective, they require expensive instrumentation, highly trained personnel and cannot be used for on-site analysis. Therefore, analytical methods for metals analysis that are simple, portable, and reliable are still needed. Colorimetric methods for metal detections have shown great potential in this field. This method can simply, conveniently and most importantly can observe by the naked eye. Porphyrin derivative compound has been widely used in analytical chemistry as chromogenic reagents for metal ion detection. Recently, porphyrin derivative compounds have been developed as optical sensors for metal detections. One of the most common detection motif used in μPADs is a colorimetric method using specific reagents to identify and quantify analytes in the sample. In this work, a distance-based μPADs has been developed using porphyrin derivative as the colorimetric reagent for metal detection. As preliminary study, interaction of three cationic porphyrins: meso-tetrakis(Nmethylpyridinium- 4-yl)porphyrin (TMPyP), meso-tetrakis(1,3- dimethylimidazolium-2-yl)porphyrin (TDMImP), and meso-tetrakis(1,2- dimethylpyrazolium-4-yl)porphyrin (TDMPzP) with metals ion (Pb, Cd, Hg, Sn, As, dan Cu) have been performed computationally using DFT method. DFT global chemical reactivity descriptors were calculated and used to predict their relative stability and reactivity. The result shows that M-TDMPzP has the highest chemical hardness and the lowest electrophilicity compare to M-TMPyP and M-TDMImP, iv indicating reaction of TDMPzP with metals will form a more stable complex. TDMPzP was continued to synthesized. TDMPzP was synthesized using Adler method in a salt form. A pure deep purple microcrystalline solid with yield 96,8% was obtained. This compound is soluble in water and analysis using UV-Vis spectrophotometry, NMR, and elemental analysis was performed for characterization. The characterization of the interaction of TDMPzP with metal ions was investigated by adding various kind of metals ion to the TDMPzP solution at different pH values. The colorimetric sensing ability of TDMPzP indicates that it was selective for Cu2+ detection in pH 2-4. JobÃ‚Â’s Plot analysis suggest that a stoichiometry of TDMPzPCu complex is 1:1 with binding constant 4,15 x 105 M-1. The selectivity of TDMPzP for Cu2+ in acidic solution makes it a good candidate to be applied in developing a distance-based μPADs for Cu2+. The lower measurable limit for this distance-based measurement for Cu2+ detection was at 1 mg L-1 which is in accordance with the regulation by US EPA and WHO guidelines for drinking water quality. The interference study results indicate the selectivity of μPADs to Cu2+ over other metal ions. Application of this system for real drinking water sample showed a good agreement between distance-based μPADs with ICP-MS. The recoveries were obtained with relative standard deviations of less than 10% All of these results suggest that TDMPzP as a colorimetric reagent was successfully applied on distance-based μPADs for determination of Cu2+ in drinking water samples. This method is simple, rapid, cost-effective, instrument-free, and selective for on-site Cu2+ analysis in aqueous medium